The Effectiveness of SEMA Number 3 of 2018 in Strengthening the Legal Protection of Iddah and Mut'ah Alimony Claims for Divorced Widows (Study of Decision Number 238/Pdt.G/2024/PA. Mn) - Agus Widyanto; Mohammad Muhibbin; Diyan Isnaeni (Vokatek: Jurnal Pengabdian Masyarakat, 2026)
This study examines the role of Supreme Court Circular Letter Number 3 of 2018 in protecting a wife’s rights to iddah and mut’ah maintenance in wife-initiated divorce, with particular reference to Decision Number 238/Pdt.G/2024/PA.Mn. This study employed doctrinal legal research using statutory and case approaches. The primary legal materials included Decision Number 238/Pdt.G/2024/PA.Mn, Law Number 1 of 1974 as amended by Law Number 16 of 2019, the Compilation of Islamic Law, Supreme Court Regulation Number 3 of 2017, and Supreme Court Circular Letter Number 3 of 2018. Secondary legal materials consisted of relevant books and scholarly articles. The legal materials were analysed through legal interpretation and content analysis, focusing on the recognition of post-divorce rights, the application of the Circular Letter in judicial reasoning, the proportionality of the awarded maintenance, and the enforceability of the judgment. The findings show that the court explicitly relied on Supreme Court Circular Letter Number 3 of 2018 after finding insufficient evidence that the plaintiff had committed nusyuz. The court awarded IDR 7,500,000 in iddah maintenance and IDR 16,000,000 in mut’ah. These findings demonstrate normative recognition and adjudicative protection of women’s post-divorce economic rights. However, enforcement-level effectiveness could not be established because no verified evidence of actual payment or execution was available. Therefore, the Circular Letter functions as an interpretive judicial guideline, although its broader effectiveness cannot be generalised from a single decision.